2019
DOI: 10.1055/a-0809-5044
|View full text |Cite
|
Sign up to set email alerts
|

Study of DNA-Binding Activity and Antibacterial Effect of Escitalopram Oxalate, an Extensively Prescribed Antidepressant

Abstract: Escitalopram oxalate (EO) is considered as one of the extensively prescribed antidepressant drug in Turkey and some other countries, therefore this research was aimed to study the interaction of the drug with DNA and study of the substance effect on bacterial growth. The absorption value of the drug solution at 238 nm was increased when DNA was added gradually to it and it showed hyperchromism effect. The value obtained for DNA binding constant (Kb) was 0.035 M −1. When we added the CuCl2 2H2O to the mixture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this research, all of ve hydrogen bonds shown in Dexamethasone-DNA docked model had a donor-acceptor distance ranging from 2.62 to 3.07 A˚ and one of them had 3.27 A˚. DNA in a human cell undergoes several thousand to a million damaging events per day, generated by both external (exogenous) and internal metabolic (endogenous) processes (Valipour et al, 2019). In order to explore DNA damage caused by chemicals, one of the inexpensive, rapid, and valuable method is incubation of a supercoiled plasmid DNA with the selected chemical followed by agarose gel electrophoresis( ) was as 5.12-21.03 nmol/L and 2.5-509.6 nmol/L, respectively.…”
Section: Interactionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this research, all of ve hydrogen bonds shown in Dexamethasone-DNA docked model had a donor-acceptor distance ranging from 2.62 to 3.07 A˚ and one of them had 3.27 A˚. DNA in a human cell undergoes several thousand to a million damaging events per day, generated by both external (exogenous) and internal metabolic (endogenous) processes (Valipour et al, 2019). In order to explore DNA damage caused by chemicals, one of the inexpensive, rapid, and valuable method is incubation of a supercoiled plasmid DNA with the selected chemical followed by agarose gel electrophoresis( ) was as 5.12-21.03 nmol/L and 2.5-509.6 nmol/L, respectively.…”
Section: Interactionmentioning
confidence: 73%
“…UVvisible spectroscopy is the most common method to study drug-DNA interaction. In the spectrum of DNA hypochromic effects occurred due to changes in the conformation and structure of DNA, after binding of a drug to DNA(Valipour, Yilmaz, & Valipour, 2019). A hyperchromic effect is due to the binding of chemicals to DNA which might result in the unwinding of DNA helix(Tabassum, Chandra Sharma, Arjmand, & Azam, 2010).…”
mentioning
confidence: 99%
“…UV-visible spectroscopy is the most common and convenient way to study the interaction between chemicals and double stranded DNA. 35 The band at 260 nm of DNA arises due to the π-π* transitions of DNA bases. "Hyperchromic" effect and "hypochromic" effect are the spectra features of DNA due to its double helical structure.…”
Section: Discussionmentioning
confidence: 99%
“…One of the inexpensive, fast and valuable methods to study the DNA-breaking activity of chemicals, is the treatment of plasmid DNA with the chemicals and analyze it in agarose gel electrophoresis (21,22). The native conformation of pUC-19 plasmid DNA is supercoil.…”
Section: Discussionmentioning
confidence: 99%